Impact of Inflammation on Midazolam Metabolism in Severe COVID‐19 Patients. Issue 5 (27th July 2022) - Le Carpentier, Edouard Charles; Canet, Emmanuel; Masson, Damien; Martin, Maëlle; Deslandes, Guillaume; Gaultier, Aurélie; Dailly, Éric; Bellouard, Ronan; Gregoire, Matthieu
Abstract : Midazolam is a benzodiazepine frequently used for sedation in patients hospitalized in the intensive care unit (ICU) for coronavirus disease 2019 (COVID‐19). This drug is primarily metabolized by cytochrome P450 3A (CYP3A) isoenzymes. Several studies have suggested that inflammation, frequently observed in these patients, could modulate CYP3A activity. The objective of this work was to study the impact of inflammation on midazolam pharmacokinetics in patients with COVID‐19. Forty‐eight patients hospitalized in the ICU for COVID‐19 and treated with midazolam administered by continuous infusion were included in this study. Midazolam and α‐hydroxymidazolam concentrations were measured and patient data, including the use of CYP3A inhibitors, were collected. Total and unbound concentrations of midazolam and α‐hydroxymidazolam were measured in plasma using a validated liquid‐chromatography coupled with mass spectrometry method. Inflammatory condition was evaluated by C‐reactive protein (CRP) level measurement. Both drug concentrations and CRP measurements were performed on 354 plasma samples. CRP elevation was significantly associated with the α‐hydroxymidazolam/midazolam plasma ratio decrease, whether for the unbound fraction or for the total fraction. Conversely, inflammation was not associated with protein binding modifications. Logically, α‐hydroxymidazolam/midazolam plasma ratio was significantly reduced when patients were treated with CYP3A inhibitors. In this study, we showed that inflammation probably reduces the metabolism of midazolam by CYP3A. These results suggest that molecules with narrow therapeutic margins and metabolized by CYP3A should be administrated with care in case of massive inflammatory situations.